2023
DOI: 10.1123/ijsnem.2022-0131
|View full text |Cite
|
Sign up to set email alerts
|

Does Caffeine Increase Fat Metabolism? A Systematic Review and Meta-Analysis

Abstract: Whether caffeine (CAF) increases fat metabolism remains debatable. Using systematic review coupled with meta-analysis, our aim was to determine effects of CAF on fat metabolism and the relevant factors moderating this effect. Electronic databases PubMed, SPORTDiscus, and Web of Science were searched using the following string: CAF AND (fat OR lipid) AND (metabolism OR oxidation). A meta-analytic approach aggregated data from 94 studies examining CAF’s effect on fat metabolism assessed by different biomarkers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…This could be because untrained individuals have a greater window of improvement to achieve performance, whereas trained subjects may have a greater degree of adaptation and lower margin for improvement through nutritional interventions, limiting the potential of caffeine to enhance fat oxidation. However, research can also be found reflecting an ergogenic effect of caffeine of similar magnitude and an effect on fat oxidation derived from caffeine intake in highly trained athletes and less-trained individuals [ 5 , 16 ]. Therefore, more research is needed to find out whether the effect of caffeine on the rate of fat oxidation is indeed dependent on the level of training or if this is just an artefact of the number of studies that used either type of participant.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This could be because untrained individuals have a greater window of improvement to achieve performance, whereas trained subjects may have a greater degree of adaptation and lower margin for improvement through nutritional interventions, limiting the potential of caffeine to enhance fat oxidation. However, research can also be found reflecting an ergogenic effect of caffeine of similar magnitude and an effect on fat oxidation derived from caffeine intake in highly trained athletes and less-trained individuals [ 5 , 16 ]. Therefore, more research is needed to find out whether the effect of caffeine on the rate of fat oxidation is indeed dependent on the level of training or if this is just an artefact of the number of studies that used either type of participant.…”
Section: Discussionmentioning
confidence: 99%
“…In this latter meta-analysis [ 16 ], the effect of combining caffeine with fasting periods shorter and longer than 3 h before exercise was analysed and the report confirmed that caffeine enhances fat metabolism, independently of the fasting period used before exercise. However, this meta-analysis [ 16 ] included studies with very different natures, with a mix of studies carried out at rest and during exercise and with very diverse methods to assess fat metabolism (gas exchange, blood metrics of triglycerides, FFA, and glycerol, among others). Additionally, an increase in fat metabolism induced by caffeine is not per se linked with higher fat oxidation within the working muscle, as the potential higher release of FFA induced by caffeine (i.e., lipolytic effect) must be accompanied by a higher reliance on fat in the mitochondria of the working muscle.…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…According to a meta-analysis by Conger et al [35], caffeine significantly promoted fat metabolism that was operationalized by RER (ES = 0.19). Compared to the BL phase, the RER values of both subjects decreased in the CAF (0.83) and ALL (0.84-0.85) phases and thus, could indicate increased fat metabolism.…”
Section: Discussionmentioning
confidence: 99%